The Effect of Entrepreneurial Knowledge on Entrepreneurial Intention with Perceived Desirability, Perceived Social Norms, and Perceived Feasibility as Mediating Variable - Agnes Yunike Putri; Andi Wijaya (Graduate Program of Universitas Tarumanagara, 2023)
This study was conducted to determine the effect of Entrepreneurial knowledge on perceived desirability, perceived social norms and perceived feasibility and their impact on entrepreneurial intention. This study uses the main theory of the theory of the theory of planned behavior. The research method chosen is a quantitative research method. The data processing method used is partial least squares. The results show the Entrepreneurial knowledge affects perceived desirability, entrepreneurial knowledge affects perceived social, Entrepreneurial knowledge affects perceived feasibility, perceived desirability affects interest in entrepreneurship. Perceived social norms affect interest in entrepreneurship, perceived feasibility does not affect interest in entrepreneurship. Perceived desirability mediates the effect of entrepreneurial knowledge on entrepreneurial interest. Perceived feasibility does not mediate the effect of entrepreneurial knowledge on entrepreneurial interest.